The use of inhaled corticosteroid in preschool wheezers: what's the point today? - Coghi Alessandra; Paiola Giulia; Tenero Laura; Piacentini Giorgio L (BMC, 2009)
Abstract Among the preschool children who wheeze two different groups can be identify: children who have a viral infection and those who respond to multiple triggers, such as exercise or allergens. To distinguish between these different phenotypes of wheezing, and consequently choose therapy represents a major challenge for pediatricians. Transient wheezers conditions do not improve with maintenance treatment with ICS. On the other hand they are definitely useful in children with wheeze/asthma. Increasing evidence is in favor of the potential role of leukotriene receptor antagonists in preschool children with recurrent wheezing. Oral steroid has been demonstrated not to be indicated to control acute wheezing, unless severe disease is expected in non-atopic children. The early phenotyping of preschool wheezers, upon which the appropriate treatment should be based, represents a challenging issue in the paediatric practice.